AN ANALYSIS OF ADVANCE LEVEL STUDENTS TO PERFORM THEIR SPEAKING - Harya, Trisna Dinillah; Septiyana, Linda; Sunarwan, Aisyah (STKIP PGRI Bandar Lampung, 2021)
This research aims to identify and describe about the students’ problem when they speak English. this was because the advanced level Student of University couldn’t speak well when they perform their Proposal Seminar and Also Final Examination at the State Islamic Institute of Metro. The data were taken by having interview with 10 students, interview with the Head of English Education Study Prgram, and questionnaire. The result show that most students from advanced level student couldn’t speak English well when they have their proposal seminar and Final Examination or Munaqosyah was because they wer too worry about making mistakes on their performance because they don’y have enough vocabulary and grammar mstery so it will give impact to their pronunciation and confidence.